Correlation between Onset Oxidation Temperature (OOT) and Fourier Transform Infrared Spectroscopy (FTIR) for monitoring the restabilization of Recycled Low-density Polyethylene (LDPE) - Adhemar Ruvolo-Filho; Tadeu Luiz Alonso Pelozzi (Polímeros, 2013)
In this work a new method was developed for monitoring the oxidative stability of restabilized and non-restabilized low-density polyethylene (LDPE) during multiple extrusion cycles. The method is based on correlations between Fourier Transform Infrared spectroscopy (FTIR) and Onset Oxidation Temperature (OOT). Non-linear calibration curves correlating the concentration of primary or secondary antioxidants and the OOT values were obtained.